2013
DOI: 10.1002/app.39579
|View full text |Cite
|
Sign up to set email alerts
|

Biobased hyperbranched shape‐memory polyurethanes: Effect of different vegetable oils

Abstract: Hyperbranched polyurethanes were synthesized from poly(e-caprolactone) diol as a macroglycol, butanediol as a chain extender, a monoglyceride of a vegetable oil (Mesua ferrea, castor, and sunflower oils separately) as a biobased chain extender, triethanolamine as a multifunctional moiety, and toluene diisocyanate by a prepolymerization technique with the A 2 1 B 3 approach. The structure of the synthesized hyperbranched polyurethanes was characterized by 1 H-NMR and X-ray diffraction studies. M. ferrea L. seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 28 publications
5
54
0
Order By: Relevance
“…The study showed that the characteristic (composition and structure of fatty acids) of the vegetable oils has a prominent role in the control of ultimate properties, including the shape memory and biological behaviors of such hyperbranched polyurethanes. Among Mesua ferrea, sunflower, and castor oils, Mesua ferrea L. seed oil-based hyperbranched polyurethane showed the highest thermal stability, whereas the castor oil-based one exhibited the highest tensile strength with same composition and structure of other components in the polymers (54). Although all such hyperbranched polyurethanes showed good shape fixity, the castor oil-based polyurethane showed the highest shape recovery (54).…”
Section: Methods Preparative Methods Both For the Bio-based Hyper-mentioning
confidence: 95%
See 4 more Smart Citations
“…The study showed that the characteristic (composition and structure of fatty acids) of the vegetable oils has a prominent role in the control of ultimate properties, including the shape memory and biological behaviors of such hyperbranched polyurethanes. Among Mesua ferrea, sunflower, and castor oils, Mesua ferrea L. seed oil-based hyperbranched polyurethane showed the highest thermal stability, whereas the castor oil-based one exhibited the highest tensile strength with same composition and structure of other components in the polymers (54). Although all such hyperbranched polyurethanes showed good shape fixity, the castor oil-based polyurethane showed the highest shape recovery (54).…”
Section: Methods Preparative Methods Both For the Bio-based Hyper-mentioning
confidence: 95%
“…Among Mesua ferrea, sunflower, and castor oils, Mesua ferrea L. seed oil-based hyperbranched polyurethane showed the highest thermal stability, whereas the castor oil-based one exhibited the highest tensile strength with same composition and structure of other components in the polymers (54). Although all such hyperbranched polyurethanes showed good shape fixity, the castor oil-based polyurethane showed the highest shape recovery (54).…”
Section: Methods Preparative Methods Both For the Bio-based Hyper-mentioning
confidence: 95%
See 3 more Smart Citations